Observed survival benefit of mild therapeutic hypothermia reanalysing the Circulation Improving Resuscitation Care trial. (16th May 2017) - Nürnberger, Alexander; Herkner, Harald; Sterz, Fritz; Olsen, Jan‐Aage; Lozano, Michael; van Grunsven, Pierre M.; Lerner, E. Brooke; Persse, David; Malzer, Reinhard; Brouwer, Marc A.; Westfall, Mark; Souders, Chris M.; et al.
Abstract: Background: Mild therapeutic hypothermia is argued being beneficial for outcome after cardiac arrest. Materials and methods: Retrospective analysis of Circulation Improving Resuscitation Care (CIRC) trial data to assess if therapeutic cooling to 33 ± 1 °C core temperature had an association with survival. Of 4231 adult, out‐of‐hospital cardiac arrests of presumed cardiac origin initially enrolled, eligibility criteria for therapeutic hypothermia were met by 1812. Logistic regression was undertaken in a stepwise fashion to account for the impact on outcome of each significant difference and for the variable of interest between the groups. Results: Out‐of‐ and in‐hospital cooled were 263 (15%), only after admission cooled were 230 (13%) and not cooled were 357 (20%) patients. The group cooled out of‐ and in hospital had 98 (37%) survivors as compared to the groups cooled in hospital only [80 (35%)] and of those not cooled [68 (19%)]. After adjusting for known covariates (sex, age, witnessed cardiac arrest, no‐ and low‐flow time, shockable initial rhythm, random allocation, bystander cardiopulmonary resuscitation and percutaneous coronary intervention), the odds ratio for survival comparing no cooling to out‐of‐ plus in‐hospital cooling was 0·53 [95% confidence interval (CI): 0·46–0·61, P < 0·001], and comparing to in‐hospital cooling only was 0·67 (95% CI: 0·50–0·89, P = 0·006). Conclusion: Mild therapeutic hypothermia initiated out of hospital and/or in hospital was associated with improved survival within this secondary analysis of the CIRC cohort compared to no therapeutic hypothermia.